2013
DOI: 10.1088/0004-637x/772/1/49
|View full text |Cite
|
Sign up to set email alerts
|

DO QUIESCENT AND ACTIVE GALAXIES HAVE DIFFERENTMBH*RELATIONS?

Abstract: To investigate the validity of the assumption that quiescent galaxies and active galaxies follow the same black hole mass (M BH )-stellar velocity dispersion (σ * ) relation, as required for the calibration of M BH estimators for broad line AGNs, we determine and compare the M BH -σ * relations, respectively, for quiescent and active galaxies. For the quiescent galaxy sample, composed of 72 dynamical M BH measurements, we update σ * for 28 galaxies using homogeneous H-band measurements that are corrected for g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
215
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(239 citation statements)
references
References 79 publications
22
215
1
1
Order By: Relevance
“…For comparison, the residual of the relation of Kormendy & Ho (2013, solid grey line) is also reported. As the relation of Woo et al (2013) is the reference for the calibration of the f -factor 4.31 that we are using, the average residual in BH mass (0.00 ± 0.09) and stellar velocity dispersions (0.00 ± 0.02) in the RM AGN1 are, as expected, consistent with zero. On the contrary, the average residual for AGN2 is ∆ log M BH = −0.99 ± 0.37 or equivalently ∆ log σ ⋆ = 0.14 ± 0.04.…”
Section: Stellar Velocity Dispersion Measurementssupporting
confidence: 71%
See 2 more Smart Citations
“…For comparison, the residual of the relation of Kormendy & Ho (2013, solid grey line) is also reported. As the relation of Woo et al (2013) is the reference for the calibration of the f -factor 4.31 that we are using, the average residual in BH mass (0.00 ± 0.09) and stellar velocity dispersions (0.00 ± 0.02) in the RM AGN1 are, as expected, consistent with zero. On the contrary, the average residual for AGN2 is ∆ log M BH = −0.99 ± 0.37 or equivalently ∆ log σ ⋆ = 0.14 ± 0.04.…”
Section: Stellar Velocity Dispersion Measurementssupporting
confidence: 71%
“…Table 1 lists the general properties of the final sample of 13 AGN2 with measured σ ⋆ and virial BH masses, which have all been calculated with solution a3 of Table 4 of Ricci et al (2017) assuming an average virial factor f = 4.31. This virial factor has been derived by Grier et al (2013) by requiring that RM AGN1 reproduce the M BH − σ ⋆ relation found in quiescent galaxies by Woo et al (2013). In all the following analyses, we excluded Table 1.…”
Section: Sample Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method employs the virial relation M• = f RBLR∆V 2 /G, where the broad line cloud velocity ∆V is derived from the broad emission line width, f is a scale factor that accounts for the geometry and kinematics of the BLR (usually calibrated by scaling to the local M• −σ * relationship (e.g. Onken et al 2004;Woo et al 2010;Woo et al 2013), and RBLR is the broad line region size. While the latter can be directly measured via reverberation mapping (e.g.…”
Section: Black Hole Massesmentioning
confidence: 99%
“…We use their measurements for L 5100 and σ Hβ and apply the recent scale factor f = 5.9 for active galaxies (Woo et al 2013). The resulting black hole mass for HE 1029-1831 is log(M BH /M ) = 7.4.…”
Section: The Central Black Holementioning
confidence: 99%